2023
DOI: 10.1002/oby.23810
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of metabolic syndrome traits on telomere length: a Mendelian randomization study

Abstract: Objective: Observational studies have reported bidirectional associations between metabolic syndrome (MetS) traits and short leukocyte telomere length (LTL), a TL marker in somatic tissues and a proposed risk factor for age-related degenerative diseases. However, in Mendelian randomization studies, longer LTL has been paradoxically associated with higher MetS risk. This study investigated the hypothesis that shorter LTL might be a consequence of metabolic dysfunction.Methods: This study undertook univariable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(103 reference statements)
1
6
0
Order By: Relevance
“…The second step of our MR analysis provided evidence that a genetically predicted lower BMI was associated with longer TL. Several published MR studies have reported causal evidence for BMI as a risk factor for TL or related phenotypes ( 86 , 87 ), consistent with the estimations from the second step of our mediation analysis. Mechanistically, obesity-related metabolic dysregulation leads to oxidative stress, resulting in telomere shortening ( 88 ).…”
Section: Discussionsupporting
confidence: 89%
“…The second step of our MR analysis provided evidence that a genetically predicted lower BMI was associated with longer TL. Several published MR studies have reported causal evidence for BMI as a risk factor for TL or related phenotypes ( 86 , 87 ), consistent with the estimations from the second step of our mediation analysis. Mechanistically, obesity-related metabolic dysregulation leads to oxidative stress, resulting in telomere shortening ( 88 ).…”
Section: Discussionsupporting
confidence: 89%
“…Hence, the observed disparity in their outcomes could be attributed to the aforementioned factors. Loh et al [ 28 ] found a significant negative correlation between BMI and telomere length through Mendelian randomization (MR) analysis; however, when it came to waist-to-hip ratio (WHR), the causal association with telomere length was not statistically significant. Notably, there existed a failure to investigate the inverse relationship in that study, with WC and other biological age indicators not being taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…These associations persist even after a six-year follow-up [ 12 ]. Mendelian randomization study revealed a paradoxical association between LTL (leukocyte telomere length) and the risk of metabolic syndrome [ 14 ]. It was observed that higher BMI (body mass index) was linked to shorter LTL, while higher levels of low-density lipoprotein cholesterol were associated with longer LTL [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization study revealed a paradoxical association between LTL (leukocyte telomere length) and the risk of metabolic syndrome [ 14 ]. It was observed that higher BMI (body mass index) was linked to shorter LTL, while higher levels of low-density lipoprotein cholesterol were associated with longer LTL [ 14 ]. Obesity may be linked to shorter LTL through the mechanisms of increased subclinical inflammation and lower circulating levels of linoleic acid [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation